Stereotactic Radiosurgery Outcomes in Medically and Surgically Failed or Nonsurgical Candidates with Medically Failed Prolactinomas: A Systematic Review and Meta-Analysis - Yagnik, Karan J.; Erickson, Dana; Bancos, Irina; Choby, Garret; Laack, Nadia; Van Gompel, Jamie J. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Prolactinomas are treated with dopamine agonists (DAs) as first-line therapy and transsphenoidal surgery as an alternative approach for medically failed tumors. We sought to summarize the efficacy of stereotactic radiosurgery (SRS) in the medically and surgically failed prolactinomas as well as in nonsurgical candidates with medically failed prolactinomas by systematic review and meta-analysis.Method A literature search was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analyses guideline.Results A total of 11 articles (total N = 709) met inclusion criteria. Thirty-three percent of patients were able to achieve endocrine remission at a mean follow-up of 54.2 ± 42.2 months with no association between stopping DA and endocrine remission. Sixty-two percent of patients were able to achieve endocrine control with DA therapy and 34% of patients were able to decrease the dose of DA dose when compared with pre-SRS DA dose at the end of the follow-up period. However, 54% of patients required DA at the end of the follow-up to control hyperprolactinemia. Ninety percent of patients were able to achieve radiologic control at the end of the follow-up in comparison to pre-SRS imagings. Furthermore, 26% of patients newly developed hypopituitarism (one or more pituitary hormones) post-SRS throughout the follow-up period.Conclusion This systematic review and meta-analysis demonstrates SRS as an effective adjunct therapy in medically failed nonsurgical candidates or surgically and medically recalcitrant prolactinomas with a 33% chance of achieving endocrine remission, 62% of patients achieved hormonal control with DA and GKRS (gamma knife radio-surgery), with a 34% chance of decreasing DA dose and 90% chance of achieving radiologic control.
Keywords: stereotactic radiosurgery; prolactinoma; gamma knife; surgically failed prolactinoma; dopamine resistance; dopamine intolerance; cavernous sinus invasion; SRS; peri-SRS DA stop